Making Words Sing and Dance: Sense, Style and Sound in Yoruba Prose Translation - Olubunmi Smith, Pamela (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractOrdinarily in prose translation, rhythm is usually not a matter of great concern for the translator. Unlike poetry, with its comparatively rigid form, prose, by its very nature, permits a free form fluidity, giving the translator a certain kind of carte blanche “prosaic” license. However, in language-driven texts, as is the case in the novels of Yoruba creative writer D.O. Fagunwa, the translator has to be ever mindful of the author's purposeful inter-linking of the aesthetic value of sound to the cognitive meaning of the text.